Persepsi dan Dampak BLT Terhadap Ekonomi Rumah Tangga di Desa Keranggan - Mahdavikia; Tiara Nabila; Orwita Andesta; Rifki, Ahmad; Rizal Iskandar; Muhammad Fauzi Aditya; Dedi Chandra (Jurnal Pendidikan Ekonomi, 2025)
This study explores the perceptions of residents in Keranggan Village regarding the Village Fund Direct Cash Assistance (BLT-DD) program and its impact on household economic conditions. The research is driven by the need to evaluate the effectiveness of social assistance policies amid persistent economic vulnerabilities, particularly in the aftermath of the COVID-19 pandemic. The main objective is to understand how beneficiaries perceive the BLT-DD program and to assess its role in supporting their economic well-being. A qualitative descriptive approach was employed, involving in-depth interviews and field observations with four beneficiaries and one village official. The findings reveal that the BLT-DD program is widely perceived as beneficial, especially in meeting daily basic needs among low-income families and elderly individuals. Some recipients also used the funds as capital for small-scale businesses. Although the assistance is seen as well-targeted and transparently administered, concerns remain about its sustainability in promoting long-term economic welfare. Beneficiaries expressed the need for complementary economic empowerment programs to reduce dependency on aid. Overall, the study suggests that while BLT-DD serves as a valuable short-term social protection mechanism, its long-term impact could be significantly enhanced through integrated and sustainable policy support.